Role of testosterone in SARS-CoV-2 infection: A key pathogenic factor and a biomarker for severe pneumonia. (July 2021) - Camici, Marta; Zuppi, Paolo; Lorenzini, Patrizia; Scarnecchia, Liliana; Pinnetti, Carmela; Cicalini, Stefania; Nicastri, Emanuele; Petrosillo, Nicola; Palmieri, Fabrizio; D'Offizi, Gianpiero; Marchioni, Luisa; Gagliardini, Roberta; et al.
Highlights: The prognosis of coronavirus diseases 2019 (COVID-19) is gender-related. TMPRSS2 plays a key role in COVID-19; androgen receptor regulates its expression. Severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) can damage the testes. Low serum testosterone at diagnosis is predictive of severe COVID-19. Low serum testosterone predicts for longer hospitalization and hyperinflammation. Abstract: Objectives: To investigate the association between sex hormones and the severity of coronavirus disease 2019 (COVID-19). Furthermore, associations between sex hormones and systemic inflammation markers, viral shedding and length of hospital stay were studied. Design and methods: This case–control study included a total of 48 male patients with COVID-19 admitted to an Italian reference hospital. The 24 cases were patients with PaO2 /FiO2 <250 mmHg and who needed ventilatory support during hospitalization (severe COVID-19). The 24 controls were selected in a 1:1 ratio, matched by age, from patients who maintained PaO2 /FiO2 >300 mmHg at all times and who may have required low-flow oxygen supplementation during hospitalization (mild COVID-19). For each group, sex hormones were evaluated on hospital admission. Results: Patients with severe COVID-19 (cases) had a significantly lower testosterone level compared with patients with mild COVID-19 (controls). Median total testosterone (TT) was 1.4 ng/mL in cases and 3.5 ng/mL in controls ( P = 0.005); median bioavailable testosterone (BioT) was 0.49 and 1.21 in cases and controls, respectively ( P = 0.008); and median calculated free testosterone (cFT) was 0.029 ng/mL and 0.058 ng/mL in cases and controls, respectively ( P = 0.015). Low TT, low cFT and low BioT were correlated with hyperinflammatory syndrome ( P = 0.018, P = 0.048 and P = 0.020, respectively) and associated with longer length of hospital stay ( P = 0.052, P = 0.041 and P = 0.023, respectively). No association was found between sex hormone level and duration of viral shedding, or between sex hormone level and mortality rate. Conclusions: A low level of testosterone was found to be a marker of clinical severity of COVID-19.